Choline Supplementation Ameliorates Behavioral Deficits and Alzheimer's Disease‐Like Pathology in Transgenic APP/PS1 Mice. Issue 18 (18th July 2019) - Wang, Yanyan; Guan, Xingying; Chen, Xuedan; Cai, Yulong; Ma, Yuanyuan; Ma, Jiming; Zhang, Qiming; Dai, Limeng; Fan, Xiaotang; Bai, Yun
Abstract : Scope: Alzheimer's disease (AD) is a detrimental neurodegenerative disease and has no known effective treatment. The essential nutrient choline potentially plays an important role in cognition. Perinatal choline supplementation (CS) is critical for memory performance. Findings have shown that postnatal choline‐containing compounds enhance memory functions in populations with memory impairments. However, whether CS can be targeted to decelerate the progression of AD remains unknown. Methods and results: APP/PS1 mice and their wild‐type littermates are fed either a control or CS diet from 2 to 11 months of age. As compared to WT mice, APP/PS1 mice on the control diet are characterized by the reduction in the number of cholinergic neurons in the basal forebrain, reduced cholinergic fiber staining intensity in the amygdala, and reduced hippocampal and cerebral cortical levels of choline and acetylcholine. CS partially prevents these changes and ameliorates cognitive deficits and anxiety. Furthermore, amyloid‐β deposition and microgliosis are decreased in the APP/PS1 mice fed a CS diet. These effects may have been due to inhibition of NLRP3 inflammasome activation and restoration of synapse membrane formation. Conclusion: These findings reveal a beneficial effect of CS on AD progression during adulthood and provide a likely therapeutic intervention for AD patients. Abstract : Choline is an essential nutrient. It is reported here that choline supplementation could alleviate cognitive deficits, anxiety, and Alzheimer's disease (AD)‐like pathology in an adult AD mouse. These effects might involve restoration of cholinergic neurons, inhibition of inflammasome activation, and restoration of synapse formation. These findings shed light on the potential preventive and therapeutic application of choline for AD.